Magnetic Hole and Its Resultant Electron Pitch‐Angle Distribution at Jupiter - C. Q. Wang; H. S. Fu; J. B. Cao; Z. Wang; W. D. Fu; Z. Z. Guo; H. Lan; T. R. Sun; Y. Wei; B. B. Ni; Z. H. Yao; B. Z. Zhang (Geophysical Research Letters)
Abstract Magnetic hole (MH), sometimes referred to as magnetic bottle, exhibits strong magnetic fields at its neck but weak magnetic fields at its belly. Such structure has been widely reported in the solar wind and the Earth's magnetosphere, but has not been reported at Jupiter. Here, for the first time, we report two MHs in the Jupiter's magnetosphere by utilizing measurements of the Juno mission, with one existing in the dawn side and the other existing in the dusk side. We find that the electron pitch‐angle distribution inside the MHs can be either cigar‐type or pancake‐type. The cigar‐type distribution probably appears at the belly of the MH, whereas the pancake‐type distribution probably appears at the neck. Our analyses of the depression of magnetic fields inside the MHs support such a conjunction. These results have advanced our understanding of the transient structure and its related electron dynamics in the giant planets' magnetosphere.